1983
DOI: 10.1109/tac.1983.1103151
|View full text |Cite
|
Sign up to set email alerts
|

An LQ-solution to a control problem associated with a solar thermal central receiver

Abstract: Ahsrruct-The linearized process dynamics of the steam boiler in a solar-powered central receiver change abruptly when clouds interfere with the sun's rays. The steam temperature regulator used to maintain proper exit steam conditions must control a system with variable structure and discontinuous state trajectories. This paper investigates the quadratic-optimal control of such a system, and gives the design equations for the optimal regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
8

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(104 citation statements)
references
References 8 publications
0
93
0
8
Order By: Relevance
“…Much more equations are also included in (1) (see, e.g., [5] and [23] The purpose of this note is to develop the Razumihkin-type theorem on pth moment input-to-state stability (ISS) of HSRSs and its applications. For definitions of pth moment stability and input-to-state stability, readers are referred to, e.g., [6], [7], [9], [11], [17], [19], [20], and [21]. Let us introduce the definition of pth moment ISS of HSRSs, which is consistent with the definition of ISS for deterministic systems (see, e.g., [9], [17], and [19]- [22]).…”
Section: Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more equations are also included in (1) (see, e.g., [5] and [23] The purpose of this note is to develop the Razumihkin-type theorem on pth moment input-to-state stability (ISS) of HSRSs and its applications. For definitions of pth moment stability and input-to-state stability, readers are referred to, e.g., [6], [7], [9], [11], [17], [19], [20], and [21]. Let us introduce the definition of pth moment ISS of HSRSs, which is consistent with the definition of ISS for deterministic systems (see, e.g., [9], [17], and [19]- [22]).…”
Section: Notationmentioning
confidence: 99%
“…Since Markov jump linear systems were firstly introduced in early 1960s (see, e.g., [16] and [25]), the hybrid systems driven by continuous-time Markov chains have been widely employed to model many practical systems where they may experience abrupt changes in system structure and parameters such as failure prone manufacturing, power systems, solar-powered systems and battle management in command, control and communication systems (see [1], [4], [14], [16], [21], and references therein). An area of particular interest has been the stability analysis of this class of hybrid systems and its applications to automatic control (see, e.g., [3], [8], and [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Athans [2] suggested that such hybrid systems would also become a basic framework in posing and solving control-related problems in Battle Management Command, Control and Communications (BM/C 3 ) systems. Hybrid systems were also considered for modeling electric power systems (Willsky and Levy [17]), the control of a solar thermal central receiver (Sworder and Rogers [16]) and the modeling of subtilin production by Bacillus subtilis (Hu, Wu and Sastry [5]). In his book [12], Mariton discussed how such hybrid systems have also emerged as a convenient mathematical framework for the formulation of various design problems in target tracking, fault tolerant control and manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…In MJSs, the random jumps in system parameters are represented by a Markov process taking values in a nite set. This class of systems may represent a large variety of processes including those in the aircraft flight control systems, manufacturing systems, communication systems, and economic systems, etc (Sowrder et al, 1983;Moerder et al, 1989;Boukas et al, 1995). Over the past decade, many important issues have been extensively studied for Markovian jump linear systems (MJLSs).…”
Section: Introductionmentioning
confidence: 99%